(X+y)+X equal X+(y+z). where X equal to -2/5,y equal to 4/3,z equal to-7/10 About the author Kennedy

Answer: yes Step-by-step explanation: but your question is (x + y) + z = x + (y + z) L. H. S. (x + y) + z = x + y + z = – 2/5 + 4/3 – 7/10 = (- 6 + 40 – 21) / 30 = (40 – 27)/30 = 13/30 R. H. S. x + (y + z) = x + y + z = 13/30 so, (x + y) + z = x + (y + z) (PROVED) if your question is (x + y) + x = x + (y + z) so they are not equal see this answer hope it will help you Reply

Answer:yes

Step-by-step explanation:but your question is (x + y) + z = x + (y + z)

L. H. S.

(x + y) + z

= x + y + z

= – 2/5 + 4/3 – 7/10 = (- 6 + 40 – 21) / 30 = (40 – 27)/30 = 13/30

R. H. S.

x + (y + z)

= x + y + z

= 13/30

so,

(x + y) + z = x + (y + z) (PROVED)

if your question is (x + y) + x = x + (y + z)

so they are not equal

see this answer hope it will help you